Failure analysis of input shaft - Mohamad Ridhwan, Ruslan (2008)
Power transmission system of vehicles consist several components which sometimes encounter unfortunate failures. In this thesis, the objective is to investigate the failure analysis of the input shaft in terms fatigue and stress. Two materials which are AISI 1045 and AISI 4145 is common material used in designing against fatigue behavior. Fatigue test were carried out on fatigue testing machine and S-N curve both materials show that when increasing load will decreased number of rotation, N. As a result, AISI 4145 is better endurance limits. In stress analysis, good estimation of the required strength of the structure, different methods can be employed to calculate stresses at these several points. For this thesis, one of the most powerful numerical technique known as “finite element method” is used to analyze a complex structure such as the input shaft. The analysis is divided by two ways which is analysis at teeth of gear and shaft. As a result, different load versus displacement of teeth and stress was carried out. The analysis for shaft also carried out according Richard Von Mises, the statement that the part not fail if σY > σVM . The shaft which is rotating in gearbox is safe in terms design.